PENGEMBANGAN MODUL BANGUN RUANG DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK SISWA KELAS V SD - Saputro, Hengkang Bara; Pratiwi, Indah (JURNAL PENDIDIKAN DASAR, 2024)
This research aims to develop a mathematics module on spatial construction material with a problem based learning model for fifth grade students at SD Muhammadiyah Sunten. This type of research is Research and Development (RD) research using the ADDIE development model. The data collection instrument used was a questionnaire. The data analysis techniques used are qualitative data and quantitative data. Validity tests are carried out by media experts, material experts and learning experts. The feasibility of the module is obtained from the results of teacher and student trials. The validation results for the module obtained an average percentage of 83.3% in the very good category, with respective results, including 1) media expert 84%; 2) material expert 84%; and 3) learning expert 82%. Trials of the module on teachers and students obtained a score of 86% from the teacher and 95.5% of the average percentage by 9 students. The final average score for the module from expert validation tests, teacher trials, and class V students was 88.26% in the very good category.Keywords: module, geometry, problem based learning model